Lipid-Reactive T Cells in Immunological Disorders of the Lung - Ryu, Seungwon; Park, Joon Seok; Kim, Hye Young; Kim, Ji Hyung (Frontiers in Immunology, 2018)
Regulation of T cell-mediated immunity in the lungs is critical for prevention of immune-related lung disorders as well as protection of the host from pathogens. While the prevalent view of pulmonary T cell responses relies on the peptide recognition by antigen receptors, called T cell receptor (TCR)s, on the T cell surface in the context of classical Major Histocompatibility Complex (MHC), novel pathways involving the presentation of lipid antigens by cluster of differentiation 1 (CD1) molecules to lipid-reactive T cells are emerging as the key players of the pulmonary immune system. Whereas the genetic conservation of group II CD1 (CD1d) in mouse and human genomes allowed numerous in vivo studies of CD1d-restricted invariant Natural Killer T (iNKT) cells in lung diseases, the physiological roles of group I CD1 (CD1a-c) in lung immunity are only recently being understood due to the development of human CD1-transgenic mice. In this review, we will discuss the current understanding of the biology of CD1-reactive T cells with a specific focus on their roles in several pulmonary disorders.